Предмет: Алгебра, автор: sanyakruzz123

выполните действия:
а) (2√3-3√2)(2√3+3√2).
б) (4-2√3)².

Ответы

Автор ответа: Orangesss
3

Ответ:

A)\ (2\sqrt{3}-3\sqrt{2})(2\sqrt{3}+3\sqrt{2}) =  (2\sqrt{3})^2-(3\sqrt{2})^2=4\cdot3-9\cdot2  =12-18=\boxed{-6.}\\\\B)\ (4-2\sqrt{3})^2 =4^2-2\cdot4\cdot2\sqrt{3}+(2\sqrt{3})^2=16-16\sqrt{3}+4\cdot3=16-16\sqrt{3}+12 =\boxed{28-16\sqrt{3}.}

Использованы формулы сокращенного умножения:

(a-b)(a+b)=a^2-b^2.\\\\(a-b)^2=a^2-2ab+b^2.


Аноним: неверно
Похожие вопросы